Pay Later Usage Behavior of Generation Z: Testing the Influence of Financial Literacy, Financial Self-Efficacy, and Financial Well-Being - Harum Silvia Kusuma Putri; Zaenal Arifin (Cita konsultindo, 2026)
This study aims to determine the effect of financial literacy, financial self-efficacy, and financial well-being on Generation Z's use of pay later services. This research conducted using a quantitative approach through an electronic questionnaire using Google Forms, targeting Generation Z from major cities on the island of Java. The testing conducted using Structural Equation Modeling (SEM) analysis with the Partial Least Square SEM (PLS-SEM) method using the SmartPLS application. The results of this research indicate that financial literacy has a negative effect on the use of pay later, while financial self-efficacy and financial well-being do not have an effect on the use of pay later.